Green Chemistry - El-Din Saleh, Hosam M.; Koller, Martin (IntechOpen, 2018)
To an increasing extent, "green chemistry" is a new chemical and engineering approach of chemistry and engineering, dedicated to make manufacturing processes and our world as a whole more sustainable world with a growing tendency. "Green chemistry" approaches are based on ecofriendly technologies, aiming to reduce or eliminate the use of solvents, or render them efficient and safer. Moreover, this scientific field is devoted to reduction or elimination of prevailing environmental and health threats, which typically accompany chemical products and traditional processes. The present book "Green Chemistry" contains 9 selected chapters, starting with a general introductory chapter on "green chemistry," and covers many recent applications and developments based on the principles of "green chemistry." This book is considered the appropriate way to communicate the advances in green materials and their applications to the scientific community. Chemists, scientists and researchers from related areas, and undergraduates involved in environmental issues and interested in approaches to improve the quality of life could find an inspiring and effective guide by reading this book.